SPECIFIC METHODOLOGY OF ROUNDWOOD EXAMINATION FOR THE PURPOSES OF PRODUCT VALUATION - T. Bokova (Теория и практика судебной экспертизы)
A methodology for roundwood examination is proposed, with an example from forensic casework illustrating how it can be used in a criminal case.